Comportamento de um sistema híbrido GNSS incorporado a dispositivos móveis na obtenção de levantamentos planimétricos com fins agrícolas - Lopes, Tiago Gonçalves (2019)
Smartphones are essentially personal computers equipped with multiple sensors. One of its most popular features is determining the user's location or navigating to a desired destination, which was trivially used only in urban areas. As its expansion was accelerated, there was also an evolution in the accuracy of its GNSS modules. The concept of connected agriculture is now being explored, allowing the farmer to monitor the performance of his machines remotely, and with automatic data transmission via cellular signal. However, little is known by the manufacturers, technical information about their location systems. Therefore, the objective of this work was to evaluate the behavior of low-cost receivers equipped with conventional GNSS technology and assisted by mobile telephony (A-GNSS), in environments characteristic of agricultural areas, which offer different levels of difficulty to obtain planimetric. In order to do so, we estimated the horizontal accuracy indexes by means of static positioning, where the treatments were composed by the combination of two factors: vegetation cover (Pasture and Pinus) and five GNSS receivers (one navigation and four smartphones), constituting a total of 10 treatments, evaluated in four replications, during a period of 10 hours of collection. After the data acquisition, the effect of the treatments was verified by Kruskal-Wallis non-parametric test, where 5% significance differences were detected among at least two of the treatments for the accuracy indexes. The Kruskal-Wallis Multiple Comparisons supplementation procedure was then performed to identify which pairs of treatments differed from each other, where there were significant differences between all combinations of vegetation cover and receiver factors. The presence of Pinus (C2) vegetation cover, independent of the receiver used, provided the greatest positional errors, reducing the number of visible satellites in the horizon, and causing loss in the quality of the geometric distribution of the satellites, being the best index of accuracy in this condition, obtained by receiver R2, indicating a possible performance improvement offered by the mobile telephone operator through the A-GNSS system. The use of a single satellite constellation (GPS) signal tracking system, available only at the R3 receiver, presented the worst accuracy indices compared to multi-constellation systems (GPS + Glonass). For the environment with pasture cover (C1) the best index of accuracy was obtained by the R1 navigation receiver, which also demonstrated greater stability and experimental precision of the data throughout the collection period. In this case, the smartphones presented unstable, with high sample variability. Finally, it was found that the R2 smartphone can successfully compete with the R1 navigation receiver, and both can be used in agriculture and forestry activities that require horizontal accuracy between 3 and 10 meters.